2008
DOI: 10.2527/jas.2007-0408
|View full text |Cite
|
Sign up to set email alerts
|

Determining an optimum lysine:calorie ratio for barrows and gilts in a commercial finishing facility1,2

Abstract: Our objective was to determine an optimum Lys:calorie ratio (g of total dietary Lys/Mcal of ME) for 35- to 120-kg barrows and gilts (Pig Improvement Company, L337 x C22) in a commercial finishing environment. Seven (3 barrow and 4 gilt) trials were conducted using randomized complete block designs (42 pens per trial, a total of 7,801 pigs). Six treatments with increasing Lys:calorie ratio were used in each study. Diets were corn-soybean meal-based with 6% choice white grease. Lysine:calorie ratios were attaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
76
2
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 17 publications
15
76
2
8
Order By: Relevance
“…The absence of effect of the levels of lysine in diets on the DFI of growing pigs (30 to 60 kg) was also observed by several authors (Fontes et al,2000;Gasparotto et al, 2001;Abreu et al, 2007;Souza et al, 2008, Main et al, 2008Zangeronimo et al, 2009;Fortes, 2009). …”
Section: Ingredientmentioning
confidence: 60%
See 1 more Smart Citation
“…The absence of effect of the levels of lysine in diets on the DFI of growing pigs (30 to 60 kg) was also observed by several authors (Fontes et al,2000;Gasparotto et al, 2001;Abreu et al, 2007;Souza et al, 2008, Main et al, 2008Zangeronimo et al, 2009;Fortes, 2009). …”
Section: Ingredientmentioning
confidence: 60%
“…However, Warnants et al (2003) and Main et al (2008) assessed pigs from 30 to 50 kg and from 43 to 70 kg, respectively, and found that animal weight gain showed quadratic increase up to the highest estimated levels of digestible lysine (0.91 and 1.09%).…”
Section: Ingredientmentioning
confidence: 99%
“…Outra inferência que pode ser feita a este respeito é a de que ao observarse aumento no consumo de alimento, fase após fase, as restrições no consumo diário de lisina tendem a aumentar em dietas com níveis limitantes do aminoácido, potencializando a queda do desempenho dos animais. Neste sentido, Main et al (2008) sugerem que as reduções no desempenho e viabilidade econômica são modestas na fase dos 35 aos 70 kg em comparação com as sanções mais graves ocorridas dos 70 kg ao abate em suínos alimentados com dietas marginalmente deficientes em lisina.…”
Section: Resultsunclassified
“…Por sua vez, Arouca et al (2007) (Kill et al, 2003) e machos não castrados (Kiefer et al, 2012). Main et al (2008) também registraram melhora no desempenho de machos castrados e fêmeas de 35 a 120 kg em função do aumento da concentração de lisina.…”
Section: Resultsunclassified
“…A deposição de tecido muscular com o consumo de energia só é eficientemente obtida se o aporte de aminoácidos, principalmente lisina, for suficiente para permitir a expressão genética do animal (Main et al, 2008). Dessa forma, suínos com altas taxas de deposição de proteína têm exigências mais altas de aminoácidos para expressar seu potencial genético de crescimento e eficiência para deposição de tecido muscular.…”
Section: Introductionunclassified